A lithium manganese iron phosphate material, a preparation method and application thereof

CN119706777BActive Publication Date: 2026-10-23SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411832476.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2026-10-23
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种磷酸锰铁锂材料及其制备方法和应用,解决现有技术中磷酸锰铁锂材料堆积密度低、导电率小和比能量低以及工艺复杂的问题

Benefits of technology

[0035]应用本发明的技术方案,通过将锰源、铁源、磷源与水球磨混合得到第一混合浆料,然后再加入锂源、焦磷酸、蔗糖球磨形成高稳定性的浆料,通过喷雾干燥得到微球结构的复合前驱体,以蔗糖为碳源,结合烧结温度优化以及加入焦磷酸在煅烧过程中对于微球结构的优化,经煅烧得到了多孔微球结构的碳包覆磷酸锰铁锂材料。一方面,制备得到的磷酸锰铁锂表面被碳层包覆,有利于提高磷酸锰铁锂颗粒中电子传导,且可以防止磷酸锰铁锂颗粒被电解液侵蚀,使得其具有较好的循环性能;另一方面,制备得到的磷酸锰铁锂材料为微米级球形粉末,可以更密集地堆积,有助于提高材料的振实密度,提高能量密度;此外,材料的多孔微球结构由于具有较大的比表面积,使得材料易接触到电解液并可以有效地用于锂存储,且多孔微球结构的高孔隙性和高电导性将促进锂离子和电子的传输,因而呈现出高倍率能力,当电流密度回到低倍率下时,可逆容量迅速恢复,显示出材料对锂离子快速嵌入/脱出的强大耐受力;再者,高稳定性的浆料通过喷雾形成Mn、Fe、P和O元素分布均匀的复合前驱体,经过进一步煅烧生成,生成Mn、Fe、P和O元素均匀分布的微球颗粒,有利于提高电池材料的离子传输速率、倍率性能、克容量以及循环可逆性能。最后,上述方法经过两次混合,一次煅烧,即可得到多孔微球结构的碳包覆磷酸锰铁锂材料,工艺简单,适用于大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706777B_ABST
    Figure CN119706777B_ABST
Patent Text Reader

Abstract

The application provides a lithium manganese iron phosphate material and a preparation method and application thereof, and the preparation method comprises the following steps: step S1, a manganese source, an iron source and a phosphorus source are mixed with water to obtain a first mixed slurry; step S2, a lithium source, pyrophosphoric acid and sucrose are ball-milled with the first mixed slurry to obtain a second mixed slurry; step S3, the second mixed slurry is subjected to spray drying treatment to obtain a microsphere-structured composite precursor; and step S4, the microsphere-structured composite precursor is calcined at a calcination temperature of 520-700 DEG C under an inert gas atmosphere to obtain the lithium manganese iron phosphate material. Based on the preparation method, the problems of low tap density, small conductivity, low specific energy and complex process of the lithium manganese iron phosphate material in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a lithium manganese iron phosphate material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries are widely used energy storage devices in energy storage, power batteries, and portable electronic devices. They offer advantages such as high operating voltage, low self-discharge, and good safety. A lithium-ion battery mainly consists of a positive electrode material, a negative electrode material, an electrolyte, a separator, and a casing. The main positive electrode materials include lithium cobalt oxide, lithium manganese oxide, nickel-manganese binary systems, nickel-cobalt-manganese ternary systems, nickel-cobalt-aluminum ternary systems, and lithium iron phosphate. Lithium iron phosphate, representing olivine-type phosphate positive electrode materials (LiMPO4, M = Fe, Co, Ni, and Mn), possesses excellent thermal and chemical stability, is environmentally friendly, non-toxic, has good cycle performance, and uses inexpensive raw materials, resulting in an excellent charge-discharge platform. Lithium iron phosphate has an olivine structure, belonging to the Pbnm orthogonal space group. The stable PO bonds in the LiFePO4 unit can suppress the generation of O2 during charge and discharge and inhibit the dissolution of the material matrix by the electrolyte, resulting in excellent safety performance. One drawback of lithium iron phosphate materials is their low voltage plateau, only 3.4V (relative to Li). + Lithium manganese phosphate (LiMnPO4) is an olivine-structured cathode material with properties similar to lithium iron phosphate. Besides sharing the same advantages in thermal and chemical stability as lithium iron phosphate, LiMnPO4 has a lower voltage plateau (4.1V, relatively lower than Li...). Therefore, although its theoretical specific capacity (170mAh / g) and actual specific capacity (150mAh / g) are relatively high, its energy density is only average. + Lithium manganese phosphate (LiMP) has a higher conductivity than lithium iron phosphate (LFP), a theoretical specific capacity close to that of LFP, and a theoretical energy density about 20% higher. However, lithium manganese phosphate has a lower conductivity (<10). -12 S / m) and lithium-ion conductivity (<10) -19 m 2 The / s is even worse than lithium iron phosphate, being at the insulator level, which seriously affects its application.

[0003] Lithium manganese iron phosphate (LiMn) 1-x Fe xLithium manganese phosphate (LMFP) is a solid solution material composed of lithium iron phosphate and lithium manganese phosphate. Similar to both lithium iron phosphate and lithium manganese phosphate, it exhibits excellent thermal and chemical stability. Furthermore, its operating voltage and energy density are higher than those of lithium iron phosphate, while its conductivity and lithium-ion conductivity are improved, making it a promising cathode material. Among various LMFP preparation processes, the solid-state method is widely used due to its simplicity, minimal equipment requirements, ease of production, and low cost. Numerous studies have focused on synthesizing uniform iron-manganese precursors, such as ferrous manganese oxalate, ferrous manganese phosphate, iron manganese phosphate, and iron manganese oxide, followed by calcination with lithium carbonate and a carbon source to prepare LMFP materials. However, the difficulty of this method lies in synthesizing uniform iron-manganese precursors and the complex process flow. Additionally, inherent defects in the material, such as low ionic conductivity, low specific energy, and small primary particle size, hinder the development of LiMn cathodes. 1-x Fe x The reduced packing density of PO4 electrode materials makes it difficult for their specific capacity, rate performance, and cycle performance to meet the requirements of practical applications, thus hindering the commercial application of lithium manganese iron phosphate materials. There is an urgent need to develop a method suitable for producing high-performance lithium manganese iron phosphate materials. Summary of the Invention

[0004] The main objective of this invention is to provide a lithium manganese iron phosphate material, its preparation method, and its application, thereby solving the problems of low packing density, low conductivity, low specific energy, and complex processing of lithium manganese iron phosphate materials in the prior art.

[0005] To achieve the above objectives, one aspect of the present invention provides a method for preparing lithium manganese iron phosphate material, comprising the following steps:

[0006] Step S1: Mix the manganese source, iron source, phosphorus source and water ball mill to obtain the first mixed slurry;

[0007] Step S2: The lithium source, pyrophosphate, sucrose and the first mixed slurry are ball-milled to obtain the second mixed slurry;

[0008] Step S3: The second mixed slurry is spray-dried to obtain a composite precursor with a microsphere structure;

[0009] Step S4: The microsphere-structured composite precursor is calcined in an inert gas atmosphere at a calcination temperature of 520-700℃ to obtain lithium manganese iron phosphate material.

[0010] Furthermore, the molar ratio of manganese in the manganese source, iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is (0.5-0.8):(0.2-0.5):1:(0.8-1.2), preferably ((0.5-0.8):(0.2-0.5):1:(0.9-1.1).

[0011] Furthermore, with the total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose being 100%, the mass of sucrose is 3%-7%.

[0012] Furthermore, with the total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose being 100%, the mass of pyrophosphate is 0.5%-2%.

[0013] Furthermore, with the total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose being 100%, the mass of water is 80% to 300%, preferably 90% to 120%.

[0014] Furthermore, the manganese source is selected from manganese carbonate. 、 One or more of manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetroxide, manganese trioxide, or manganese dioxide.

[0015] Furthermore, the iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, iron tetroxide, ferric phosphate, or ferrous phosphate.

[0016] Furthermore, the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate.

[0017] Furthermore, the lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate, or lithium sulfate.

[0018] Furthermore, in step S4, the calcination time is 4-8 hours, preferably 6 hours.

[0019] Preferably, in step S4, the calcination temperature is 580-650℃.

[0020] Preferably, in step S4, the composite precursor with microsphere structure is heated to the calcination temperature in an inert gas atmosphere at a heating rate of 3-7℃ / min.

[0021] Furthermore, in step S1, the manganese source, iron source and phosphorus source are first mixed to obtain a mixture, which is then dispersed with deionized water and ball-milled.

[0022] Preferably, in step S1, the ball milling time is 350-450 rpm and the ball milling time is 2-8 hours.

[0023] Preferably, in step S2, the ball milling time is 350-450 rpm and the ball milling time is 2-8 hours.

[0024] Preferably, in the spray drying process, the frequency of the feed peristaltic pump is 5-40Hz and the temperature is 100-110℃.

[0025] According to another aspect of the present invention, a lithium manganese iron phosphate material is provided, which is prepared according to the above-described method for preparing lithium manganese iron phosphate material. The lithium manganese iron phosphate material has a porous microsphere structure, and the porous microspheres are formed by the aggregation of primary nanoparticles, the primary nanoparticles including lithium manganese iron phosphate nanoparticles and a carbon layer coated on the surface of the lithium manganese iron phosphate nanoparticles.

[0026] Furthermore, the porous microspheres have a particle size of 10-20 micrometers.

[0027] Furthermore, the particle size of the primary nanoparticles is 50-100 nm.

[0028] Furthermore, the thickness of the carbon layer is 2-5 nm.

[0029] Furthermore, the general material composition formula of lithium manganese iron phosphate nanoparticles is LiMn 1-x Fe x PO4, where 0.2≤x≤0.5.

[0030] Furthermore, the specific surface area of ​​lithium manganese iron phosphate material is 20-25 m². 2 g -1 .

[0031] Furthermore, the tap density of lithium manganese iron phosphate material is 1-1.5 g / cm³. 3 .

[0032] According to another aspect of the present invention, a lithium manganese iron phosphate composite material is provided, comprising the lithium manganese iron phosphate material as described above.

[0033] According to another aspect of the present invention, a positive electrode is provided, the positive electrode comprising the lithium manganese iron phosphate material as described above.

[0034] According to another aspect of the present invention, a lithium-ion battery is also provided, comprising the positive electrode as described above.

[0035] By applying the technical solution of this invention, a first mixed slurry is obtained by mixing manganese source, iron source, phosphorus source and water ball milling, and then lithium source, pyrophosphate and sucrose are added and ball milled to form a highly stable slurry. The composite precursor with microsphere structure is obtained by spray drying. Using sucrose as carbon source, combined with sintering temperature optimization and the optimization of microsphere structure by adding pyrophosphate during calcination, a porous microsphere structure carbon-coated lithium manganese iron phosphate material is obtained by calcination. On the one hand, the carbon layer coating on the surface of the prepared lithium manganese iron phosphate (LMP) particles is beneficial for improving electron conduction and preventing electrolyte erosion, resulting in better cycle performance. On the other hand, the prepared LMP material is a micron-sized spherical powder, which can be more densely packed, helping to improve the tap density and energy density. In addition, the porous microsphere structure of the material has a large specific surface area, making it easy to contact the electrolyte and effectively used for lithium storage. The high porosity and high conductivity of the porous microsphere structure will promote the transport of lithium ions and electrons, thus exhibiting high rate capability. When the current density returns to a low rate, the reversible capacity recovers rapidly, demonstrating the material's strong tolerance to rapid lithium ion insertion / extraction. Furthermore, the highly stable slurry is sprayed to form a composite precursor with uniform distribution of Mn, Fe, P, and O elements. After further calcination, microsphere particles with uniform distribution of Mn, Fe, P, and O elements are generated, which is beneficial for improving the ion transport rate, rate performance, specific capacity, and cycle reversibility of the battery material. Finally, the above method, through two mixing processes and one calcination, yields carbon-coated manganese iron phosphate material with a porous microsphere structure. The process is simple and suitable for large-scale production. Attached Figure Description

[0036] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0037] Figure 1 The image shows the XRD pattern of the lithium manganese iron phosphate material prepared in Example 1.

[0038] Figure 2 The images show (a) SEM images of micron-sized secondary particles, (b) SEM images of nano-sized primary particles, and (c) EDX elemental imaging of Mn, Fe, P, and O elements in the micron-sized secondary particles of the lithium manganese iron phosphate material prepared in Example 1.

[0039] Figure 3 HR-TEM image of nanoscale primary particles in the lithium manganese iron phosphate material prepared in Example 1;

[0040] Figure 4 This is a graph showing the capacity retention rate of the battery obtained in Example 1 after 200 cycles at 1C. Detailed Implementation

[0041] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0042] As described in the background section, existing lithium manganese iron phosphate materials suffer from low packing density, low conductivity, low energy density, and complex processing. To address these issues, this invention provides a method for preparing lithium manganese iron phosphate materials, comprising the following steps: Step S1, ball milling manganese source, iron source, phosphorus source, and water to obtain a first mixed slurry; Step S2, ball milling lithium source, pyrophosphate, sucrose, and the first mixed slurry to obtain a second mixed slurry; Step S3, spray drying the second mixed slurry to obtain a microsphere-structured composite precursor; Step S4, calcining the microsphere-structured composite precursor in an inert gas atmosphere at a calcination temperature of 520-700℃ to obtain the lithium manganese iron phosphate material.

[0043] The preparation method of lithium manganese iron phosphate material based on the technical solution of the present invention involves mixing manganese source, iron source, phosphorus source and water ball milling to obtain a first mixed slurry, and then adding lithium source, pyrophosphate and sucrose ball milling to form a highly stable slurry. The composite precursor with microsphere structure is obtained by spray drying. Using sucrose as carbon source, combined with sintering temperature optimization and the optimization of microsphere structure by adding pyrophosphate during calcination, carbon-coated lithium manganese iron phosphate material with porous microsphere structure is obtained after calcination. On the one hand, the carbon layer coating on the surface of the prepared lithium manganese iron phosphate (LMP) particles is beneficial for improving electron conduction and preventing electrolyte erosion, resulting in better cycle performance. On the other hand, the prepared LMP material is a micron-sized spherical powder, which can be more densely packed, helping to improve the tap density and energy density. In addition, the porous microsphere structure of the material has a large specific surface area, making it easy to contact the electrolyte and effectively used for lithium storage. The high porosity and high conductivity of the porous microsphere structure will promote the transport of lithium ions and electrons, thus exhibiting high rate capability. When the current density returns to a low rate, the reversible capacity recovers rapidly, demonstrating the material's strong tolerance to rapid lithium ion insertion / extraction. Furthermore, the highly stable slurry is sprayed to form a composite precursor with uniform distribution of Mn, Fe, P, and O elements. After further calcination, microsphere particles with uniform distribution of Mn, Fe, P, and O elements are generated, which is beneficial for improving the ion transport rate, rate performance, specific capacity, and cycle reversibility of the battery material. Finally, the above method, through two mixing processes and one calcination, yields carbon-coated manganese iron phosphate material with a porous microsphere structure. The process is simple and suitable for large-scale production.

[0044] To obtain high-performance lithium manganese iron phosphate materials, in some embodiments, the molar ratio of manganese in the manganese source, iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is (0.5-0.8):(0.2-0.5):1:(0.8-1.2), preferably (0.5-0.8):(0.2-0.5):1:(0.9-1.1), in order to obtain high-yield and high-purity LiMn. 1-x Fe x PO4.

[0045] In some embodiments, the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose is 100%, with sucrose accounting for 3%-7% of the mass. Using sucrose as a carbon source, through optimization of its addition amount and control of the sintering temperature, it is beneficial to prevent excessive growth of primary nanoparticles and large-scale aggregation of primary particles. As a natural carbon source, sucrose forms a more uniform and continuous carbon layer during thermal decomposition. At this addition amount, a more uniform carbon coating layer and a regular porous microsphere structure can be obtained.

[0046] In some embodiments, based on the total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose (100%), the mass of pyrophosphate is 0.5%-2%. The addition of pyrophosphate can improve the crystallinity of lithium manganese iron phosphate, affecting the microstructure of the final product, including particle size, shape, and elemental distribution, thereby affecting the performance of lithium manganese iron phosphate as a battery material. Furthermore, pyrophosphate can promote the pyrolysis of carbon sources (such as sucrose) during calcination, which is beneficial for forming a uniform carbon coating layer. At this addition amount, a more uniform and regular porous microsphere structure and a uniform carbon coating layer can be obtained.

[0047] In some embodiments, the water content is 80% to 300% of the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose, which is beneficial for obtaining a stable slurry system for spray drying and for achieving higher drying efficiency. Preferably, the water content is 90% to 120%.

[0048] In one embodiment, the manganese source is selected from one or more of manganese carbonate, manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetroxide, manganese trioxide, or manganese dioxide.

[0049] In one embodiment, the iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, iron tetroxide, ferric phosphate, or ferrous phosphate.

[0050] In one embodiment, the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate.

[0051] In one embodiment, the lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate, or lithium sulfate.

[0052] In a preferred embodiment, in step S4, the calcination time is 4-8 hours. The temperature and time during the calcination process affect the carbon structure and coating effect. The calcination temperature also affects the degree of primary particle aggregation and the primary particle growth rate. In addition, pyrophosphate can be used as a flux to lower the melting point of the entire system, making the raw materials easier to melt and mix. This helps to form lithium manganese iron phosphate particles with uniform distribution of elements at the above time. The above calcination time is conducive to obtaining a regular, highly dispersed porous microsphere structure with uniform distribution of Mn, Fe, P and O elements, as well as a uniform and continuous carbon coating layer with good conductivity. The preferred calcination time is 6 hours to form regular porous microspheres with appropriate particle size and high crystallinity, and to reduce energy consumption. The preferred calcination temperature is 580-650℃, which facilitates the formation of a uniform and continuous conductive carbon layer and reduces excessive agglomeration and growth of primary particles, resulting in a more regular porous microsphere structure and a lithium manganese iron phosphate material with high porosity, high electrical conductivity, and high tap density. Preferably, the composite precursor of the microsphere structure is heated to the calcination temperature in an inert gas atmosphere at a heating rate of 3-7℃ / min to obtain a porous microsphere structure with more regular morphology and high particle crystallinity.

[0053] To improve the dispersion effect of the first mixed slurry, in some embodiments, in step S1, the manganese source, iron source and phosphorus source are first mixed to obtain a mixture, the mixture is dispersed with deionized water and then ball-milled; in order to fully disperse the manganese source, iron source and phosphorus source, in step S1, the ball milling time is 350-450 rpm and the ball milling time is 2-8 h; in order to obtain a highly stable second mixed slurry, it is preferred that in step S2, the ball milling time is 350-450 rpm and the ball milling time is 2-8 h.

[0054] According to another aspect of the present invention, a lithium manganese iron phosphate material is provided, which is prepared according to the above-described method for preparing lithium manganese iron phosphate material. The lithium manganese iron phosphate material has a porous microsphere structure, and the porous microspheres are formed by the aggregation of primary nanoparticles, including lithium manganese iron phosphate nanoparticles and a carbon layer coated on the surface of the lithium manganese iron phosphate nanoparticles.

[0055] In some embodiments, the porous microspheres have a particle size of 10-20 micrometers to obtain higher packing density and higher energy density.

[0056] In some embodiments, the particle size of the primary nanoparticles is 50-100 nm. The smaller primary crystal particle size can improve the conductivity of the material and shorten the distance between pores. The interconnected three-dimensional pore channels are beneficial to shorten the lithium ion insertion / extraction distance, and the material has high rate performance. Moreover, the lithium manganese iron phosphate material has a porous microsphere structure and the aforementioned primary particle size, which makes it have both high energy density and battery performance.

[0057] In some embodiments, the thickness of the carbon layer is 2-5 nm to obtain better electrical conductivity.

[0058] In some embodiments, the general material composition formula of lithium manganese iron phosphate nanoparticles is LiMn. 1-x Fe x PO4, where 0.2≤x≤0.5, in order to obtain lithium manganese iron phosphate with both high capacity and high energy density.

[0059] In some embodiments, the specific surface area of ​​lithium manganese iron phosphate material is 20-25 m². 2 g -1 In order to obtain higher rate performance.

[0060] In some embodiments, the tap density of lithium manganese iron phosphate material is 1-1.5 g / cm³. 3 In order to obtain higher energy density.

[0061] According to another aspect of the present invention, a lithium manganese iron phosphate composite material is provided, comprising the lithium manganese iron phosphate material as described above.

[0062] According to another aspect of the present invention, a positive electrode is provided, comprising the lithium manganese iron phosphate material as described above. The lithium manganese iron phosphate material prepared based on the method of the present invention has high packing density, conductivity, and energy density, and possesses excellent ion transport rate, rate performance, and cycle reversibility, making it a very promising positive electrode material.

[0063] According to another aspect of the present invention, a lithium-ion battery is also provided, comprising the above-described positive electrode, thereby obtaining a lithium-ion battery with high capacity, high energy, high-speed charge and discharge performance, as well as good safety, long life and low cost.

[0064] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0065] Example 1

[0066] A lithium manganese iron phosphate material is prepared by the following steps:

[0067] Step 1: Mix MnCO3, Fe(CH3COO)2·4H2O and H3PO4, disperse with deionized water, and then use a high-speed planetary ball mill to ball mill at 400 rpm for 5 hours to obtain the first mixed slurry.

[0068] Step 2: Add Li2CO3, pyrophosphate and sucrose to the first mixed slurry, and ball mill again at 400 rpm for 5 hours to form a highly stable second mixed slurry.

[0069] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray drying process, the peristaltic pump frequency is 15Hz and the temperature is 101℃.

[0070] Step 4: The prepared microsphere-structured composite precursor was heated to 650℃ under N2 atmosphere at a heating rate of 5℃ / min and calcined for 6 hours to obtain lithium manganese iron phosphate material LiMn. 0.8 Fe 0.2 PO4.

[0071] The molar ratio of Mn in MnCO3, Fe in Fe(CH3COO)2·4H2O, phosphorus in H3PO4, and Li in Li2CO3 is 0.8:0.2:1:1. The total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose is 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.

[0072] Example 2

[0073] A lithium manganese iron phosphate material is prepared by the following steps:

[0074] Step 1: Mix manganese acetate, ferrous oxalate and ammonium dihydrogen phosphate, disperse with deionized water, and then use a high-speed planetary ball mill to ball mill at 350 rpm for 5 hours to obtain the first mixed slurry;

[0075] Step 2: Add lithium acetate, pyrophosphate and sucrose to the first mixed slurry, and ball mill again at 350 rpm for 5 hours to form a highly stable second mixed slurry.

[0076] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray drying process, the flow rate is 20 Hz and the peristaltic pump frequency is 105 ℃.

[0077] Step 4: The prepared microsphere-structured composite precursor was heated to 580℃ under N2 atmosphere at a heating rate of 3℃ / min and calcined for 5 hours to obtain lithium manganese iron phosphate material LiMn. 0.5 Fe 0.5PO4.

[0078] The molar ratio of Mn in manganese acetate, Fe in ferrous oxalate, phosphorus in ammonium dihydrogen phosphate, and Li in lithium acetate is 0.5:0.5:1:1.1. The total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose is 100%, with pyrophosphate accounting for 0.5%, sucrose for 3%, and water for 80%.

[0079] Example 3

[0080] A lithium manganese iron phosphate material is prepared by the following steps:

[0081] Step 1: Mix manganese tetroxide, iron oxide and ammonium phosphate, disperse with deionized water and then use a high-speed planetary ball mill to ball mill at 450 rpm for 5 hours to obtain the first mixed slurry;

[0082] Step 2: Add lithium formate, pyrophosphate and sucrose to the first mixed slurry, and ball mill again at 450 rpm for 5 hours to form a highly stable second mixed slurry.

[0083] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure; during the spray drying process, the feed peristaltic pump frequency is 12Hz and the temperature is 102℃.

[0084] Step 4: The prepared microsphere-structured composite precursor was heated to 620℃ under N2 atmosphere at a heating rate of 7℃ / min and calcined for 8 hours to obtain lithium manganese iron phosphate material LiMn. 0.6 Fe 0.4 PO4.

[0085] The molar ratio of Mn in manganese tetroxide, Fe in iron oxide, phosphorus in ammonium phosphate, and Li in lithium formate is 0.6:0.4:1:0.9. Based on the total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose being 100%, the mass of pyrophosphate is 2%, the mass of sucrose is 7%, and the mass of water is 120%.

[0086] Example 4

[0087] The only difference between it and Example 1 is that the calcination temperature is 560°C, as detailed below:

[0088] A lithium manganese iron phosphate material, the preparation method includes the following steps: (1) MnCO3, Fe(CH3COO)2·4H2O and H3PO4 are mixed, dispersed with deionized water, and then ball-milled for 5 hours at 400 rpm using a high-speed planetary ball mill to obtain the first mixed slurry;

[0089] Step 2: Add Li2CO3, pyrophosphate and sucrose to the first mixed slurry, and ball mill again at 400 rpm for 5 hours to form a highly stable second mixed slurry.

[0090] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray drying process, the peristaltic pump frequency is 15Hz and the temperature is 101℃.

[0091] Step 4: The prepared microsphere-structured composite precursor was heated to 560℃ under N2 atmosphere at a heating rate of 5℃ / min and calcined for 6 hours to obtain lithium manganese iron phosphate material LiMn. 0.8 Fe 0.2 PO4.

[0092] The molar ratio of Mn in MnCO3, Fe in Fe(CH3COO)2·4H2O, phosphorus in H3PO4, and Li in Li2CO3 is 0.8:0.2:1:1. The total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose is 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.

[0093] Example 5

[0094] The only difference between it and Example 1 is that the heating rate in step four is 10°C / min.

[0095] Comparative Example 1

[0096] The only difference between it and Example 1 is that in step two, sucrose is replaced with starch.

[0097] Comparative Example 2

[0098] The only difference between it and Example 1 is that the calcination temperature in step four is 500°C.

[0099] Comparative Example 3

[0100] The only difference between it and Example 1 is that the calcination temperature in step four is 720°C.

[0101] Comparative Example 4

[0102] A lithium manganese iron phosphate material is prepared by the following steps:

[0103] Step 1: Mix MnCO3, Fe(CH3COO)2·4H2O, H3PO4, Li2CO3, pyrophosphate, sucrose and water in the same amounts as in Example 1, and then ball mill them in a high-speed planetary ball mill at 400 rpm for 10 hours to obtain a mixed slurry.

[0104] Step 2: The mixed slurry is spray-dried to form a composite precursor. During the spray drying process, the peristaltic pump frequency is 15Hz and the temperature is 101℃.

[0105] Step 3: The prepared composite precursor was heated to 650℃ under a N2 atmosphere at a heating rate of 5℃ / min and calcined for 6 hours to obtain lithium manganese iron phosphate material. The prepared lithium manganese iron phosphate material LiMn was then obtained. 0.8 Fe 0.2 PO4.

[0106] The molar ratio of Mn in MnCO3, Fe in Fe(CH3COO)2·4H2O, phosphorus in H3PO4, and Li in Li2CO3 is 0.8:0.2:1:1. The total weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose is 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.

[0107] Comparative Example 5

[0108] The only difference between it and Example 1 is that pyrophosphate was not added in step two.

[0109] Structural characterization and performance testing

[0110] I. XRD Characterization

[0111] XRD measurements of lithium manganese iron phosphate were performed using a Bruker D8 Discovery X-ray diffractometer under the following conditions: CuKα radiation was used, and the data collection range was from 10° to 80°. The LiMn prepared in Example 1... 0.8 Fe 0.2 The XRD characterization results of PO4 are as follows Figure 1 As shown, the diffraction pattern is in excellent agreement with the data in JCPDS No. 13-0336, indicating that the prepared LiMn 0.8 Fe 0.2 PO4 belongs to an orthorhombic crystal system compound with an ordered olivine structure (space group Pnma). No peaks were observed for impurity phases or amorphous carbon structures, indicating high-purity lithium manganese iron phosphate phases and low carbon content in the prepared lithium manganese iron phosphate material. The parameters of lithium manganese iron phosphate were calculated using TOPAS 5 software with Rietveld refinement, and the unit cell parameters of lithium manganese iron phosphate were obtained. The results are consistent with those reported in the literature for lithium manganese iron phosphate, and have relatively small Rw (6.9%) and Rp (5.4%) factors, indicating a good fit.

[0112] II. Scanning Electron Microscopy (SEM) Characterization and High-Resolution Transmission Electron Microscopy (HRTEM) Characterization

[0113] The morphology of lithium manganese iron phosphate materials was characterized using a scanning electron microscope (SEM, JEOL JSM-6390). LiMn prepared in Example 1 0.8 Fe 0.2 The SEM characterization results of PO4 are as follows: Figure 2 As shown. Figure 2 Figure (a) clearly shows the prepared LiMn 0.8 Fe 0.2 The PO4 material exhibits a distinct spherical morphology, with micron-sized secondary particles ranging in size from 10 to 20 micrometers. As shown in Figure (b) with a magnified view of a single micron-sized secondary particle, these particles are composed of relatively small nanometer-sized primary particles, with a particle size of approximately 50-100 nm. LiFe exhibits this micron-spherical structure. 0.2 Mn 0.8 PO4 particles can have a high packing density.

[0114] To investigate the elemental distribution in micron-sized secondary particles, energy-dispersive X-ray (EDX) elemental imaging was performed on Mn, Fe, P, and O, such as... Figure 2 As shown in Figure (c), the distribution of Mn and Fe is in good agreement with the distribution of P and O elements, indicating that the transition metals are uniformly distributed in the microspheres.

[0115] The lithium manganese iron phosphate material prepared in Example 1 was characterized by HRTEM using a transmission electron microscope (JEOL JEM-2010). Figure 3 As shown, the surface of lithium manganese iron phosphate nanoparticles is tightly wrapped by a continuous carbon layer approximately 3 nanometers thick.

[0116] Combined with SEM and HRTEM characterization, it can be seen that the lithium manganese iron phosphate material prepared in Example 1 has a porous microsphere structure. The porous microspheres are formed by the aggregation of primary nanoparticles with continuous carbon layers on their surface. The particle size of the porous microspheres is 10-20 micrometers, the shape is regular, the thickness of the conductive carbon layer is about 3nm, and the porous microsphere particles have interconnected three-dimensional pore channels inside.

[0117] III. Specific Surface Area Characterization

[0118] The specific surface area of ​​the lithium manganese iron phosphate materials prepared in the examples and comparative examples was tested using the Brunauer–Emmett–Teller (BET) method and a Quadasorb SI Automated Surface Area and Pore Size Analyzer. The results are shown in Table 1.

[0119] IV. Testing of Powder Resistivity

[0120] The powder resistivity of lithium manganese iron phosphate materials obtained in the examples and comparative examples was tested using a four-probe instrument. The test results are shown in Table 1.

[0121] V. Tap Density Test

[0122] The tap density of the lithium manganese iron phosphate materials obtained in the examples and comparative examples was tested using a tap density meter (Konta, DAT-6-220, USA). The specific steps are as follows: the sample was placed in a graduated cylinder and tapped 3000 times. The volume of the graduated cylinder after tapping was read and the tap density was calculated. The results are shown in Table 1.

[0123] VI. Electrochemical Testing

[0124] The specific steps for manufacturing lithium-ion batteries are as follows:

[0125] Positive electrode preparation: Based on a mass ratio of 100% for the positive electrode material, conductive agent, and polyvinylidene fluoride (PVDF) binder, 90% of the positive electrode material, 5% of the conductive agent, and 5% of the PVDF binder were dispersed in 1-methyl-2-pyrrolidone (NMP), and then uniformly coated onto aluminum foil. The coated aluminum foil was dried at 80°C for 60 minutes, followed by vacuum drying at 100°C for 12 hours. The dried aluminum foil was cut into circular pieces with a diameter of 12 mm to obtain the positive electrode. The loading of lithium manganese iron phosphate material on the positive electrode was approximately 5 mg / cm³. 2 .

[0126] Battery Assembly: Battery assembly was performed using a standard CR2016 button mold in an argon-filled glove box. Lithium metal was used as the negative electrode of the standard half-cell, and the prepared positive electrode sheet was used as the positive electrode. LiPF6 was dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and methyl acetate (EMC) (EC, DMC, and EMC volume ratio 1:1:1) to prepare a 1 mol / L electrolyte. -1 LiPF6 solution.

[0127] Following the above method, lithium-ion batteries were prepared using the lithium manganese iron phosphate materials prepared in the examples and comparative examples as cathode materials, and charge-discharge tests and cycle performance tests at room temperature were conducted, as detailed below:

[0128] (1) Charge and discharge test: The charge and discharge specific capacity of lithium-ion batteries were tested at 25℃ at 0.2C, 1C, 2C and 5C rates and in the voltage range of 2.0-4.5V. The specific capacity of 0.2C charging, 0.2C discharging, 0.2C first-cycle coulombic efficiency, 1C charging, 2C charging and 5C charging at 25℃ are shown in Table 1.

[0129] (2) Cyclic performance test at room temperature: 200 cycles were performed at 25℃, 1C rate and 2.0-4.5V voltage range. The capacity retention rate after 200 cycles at 1C at 25℃ is shown in Table 1.

[0130] Then, charge / discharge tests, room temperature cycle performance tests, high temperature cycle performance tests, and rate performance tests were conducted.

[0131] Table 1

[0132]

[0133] As can be seen from the data in Table 1, compared with Comparative Examples 1 to 5, the composite lithium manganese iron phosphate cathode materials prepared by the preparation methods of Examples 1 to 5 of the present invention have higher tap density, lower powder resistivity, higher charge-discharge specific capacity and higher first-cycle coulombic efficiency, and better rate performance.

[0134] A comparison of Example 1 and Comparative Example 1 shows that, compared to Comparative Example 1 which used starch as the carbon source for the carbon coating layer, Example 1, which used sucrose as the carbon source for the carbon coating layer, more easily forms a uniform and continuous carbon layer on the lithium manganese iron phosphate nanoparticles during pyrolysis. This results in a significant reduction in powder resistivity and relatively higher discharge specific capacities at 0.2C, 1C, 2C, and 5C. The capacity retention results for 200 cycles at 1C for Example 1 and Comparative Example 1 are as follows: Figure 4 As shown, the carbon source in Example 1 provides better cycle stability, and the discharge capacity can still be maintained at 97.16% after 200 cycles, while that in Comparative Example 1 is only 87.04%.

[0135] A comparison of Examples 1, 4, and Comparative Example 2 shows that, compared to the lower calcination temperature used in Comparative Example 2, the powder resistivity of the lithium manganese iron phosphate material in Examples 1 and 4 is significantly reduced, while the specific surface area, charge / discharge specific capacity, battery efficiency, and capacity retention are significantly improved, and the tap density is also higher. A comparison of Examples 1 and Comparative Example 3 shows that, compared to the higher calcination temperature used in Comparative Example 3, the powder resistivity of the lithium manganese iron phosphate material in Example 1 is significantly reduced, while the charge / discharge specific capacity, battery efficiency, and capacity retention are significantly improved. At the calcination temperatures (520-700℃) used in this application, especially at 580-650℃, it is easier to generate a uniformly connected conductive carbon layer and a regular porous microsphere structure, which is beneficial for improving the conductivity of the lithium manganese iron phosphate material.

[0136] As can be seen from the comparison between Example 1 and Comparative Example 4, under the same conditions of raw materials and calcination process, compared with the method of directly ball milling each raw material to prepare slurry in Comparative Example 4, the method of stepwise dispersion to prepare slurry in Example 1 results in a powder resistivity and electrochemical performance of lithium manganese iron phosphate that are far superior to those of Comparative Example 4.

[0137] As can be seen from the comparison between Example 1 and Comparative Example 5, under the same mixing method and calcination process, the resistivity of the lithium manganese iron phosphate powder prepared in Example 1 is much lower than that in Comparative Example 5, which did not contain pyrophosphate. The addition of pyrophosphate can promote the pyrolysis of carbon source to form a uniform and continuous carbon coating layer. Moreover, the charge-discharge specific capacity and tap density of Example 1 are much higher than those of Comparative Example 5. The addition of pyrophosphate is beneficial to the formation of a uniform and regular porous microsphere structure and carbon coating layer, which is beneficial to improving the electrochemical performance and tap density of the composite lithium manganese iron phosphate cathode material.

[0138] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that, Includes the following steps: Step S1: Mix the manganese source, iron source, phosphorus source and water ball mill to obtain the first mixed slurry; Step S2: The lithium source, pyrophosphate, sucrose and the first mixed slurry are ball-milled to obtain a second mixed slurry; Step S3: The second mixed slurry is spray-dried to obtain a composite precursor with a microsphere structure; Step S4: The composite precursor with the microsphere structure is calcined in an inert gas atmosphere at a calcination temperature of 520-700℃ to obtain lithium manganese iron phosphate material.

2. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The molar ratio of manganese in the manganese source, iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is (0.5-0.8):(0.2-0.5):1:(0.8-1.2); and / or, Based on the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose being 100%, the mass of the sucrose is 3%-7%; and / or, Based on the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate, and sucrose being 100%, the mass of the pyrophosphate is 0.5%-2%. The water content is 80% to 300% of the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose, which together constitute 100%.

3. The method for preparing lithium manganese iron phosphate material according to claim 2, characterized in that, The molar ratio of manganese in the manganese source, iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is (0.5-0.8):(0.2-0.5):1:(0.9-1.1).

4. The method for preparing lithium manganese iron phosphate material according to claim 2, characterized in that, The water content is 90% to 120% of the total weight of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose.

5. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The manganese source is selected from one or more of manganese carbonate, manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetroxide, manganese trioxide, or manganese dioxide; and / or, The iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, iron tetroxide, ferric phosphate, or ferrous phosphate. The phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate; and / or, The lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate, or lithium sulfate.

6. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, In step S4, the calcination time is 4-8 hours.

7. The method for preparing lithium manganese iron phosphate material according to claim 6, characterized in that, In step S4, the calcination time is 6 hours.

8. The method for preparing lithium manganese iron phosphate material according to claim 6, characterized in that, In step S4, the calcination temperature is 580-650℃.

9. The method for preparing lithium manganese iron phosphate material according to claim 6, characterized in that, In step S4, the composite precursor with the microsphere structure is heated to the calcination temperature at a heating rate of 3-7℃ / min under an inert gas atmosphere.

10. The method for preparing lithium manganese iron phosphate material according to any one of claims 1-9, characterized in that, In step S1, the manganese source, iron source and phosphorus source are first mixed to obtain a mixture, and the mixture is dispersed with deionized water before ball milling.

11. The method for preparing lithium manganese iron phosphate material according to claim 10, characterized in that, In step S1, the ball milling time is 350-450 rpm and the ball milling time is 2-8 hours.

12. The method for preparing lithium manganese iron phosphate material according to claim 10, characterized in that, In step S2, the ball milling time is 350-450 rpm and the ball milling time is 2-8 hours.

13. The method for preparing lithium manganese iron phosphate material according to claim 10, characterized in that, In the spray drying process, the feed peristaltic pump frequency is 5-40Hz and the temperature is 100-110℃.

14. A lithium manganese iron phosphate material, characterized in that, The lithium manganese iron phosphate material is prepared according to any one of claims 1-13. The lithium manganese iron phosphate material has a porous microsphere structure, and the porous microsphere is formed by the aggregation of primary nanoparticles. The primary nanoparticles include lithium manganese iron phosphate nanoparticles and a carbon layer coated on the surface of the lithium manganese iron phosphate nanoparticles.

15. The lithium manganese iron phosphate material according to claim 14, characterized in that, The porous microspheres have a particle size of 10-20 micrometers; and / or, The primary nanoparticles have a particle size of 50-100 nm; and / or, The thickness of the carbon layer is 2-5 nm; and / or, The lithium manganese iron phosphate nanoparticles have the general material formula LiMn. 1-x Fe x PO4, where 0.2 ≤ x ≤ 0.5; and / or, The specific surface area of ​​the lithium manganese iron phosphate material is 20-25 m²g. -1 ; and / or, The tap density of the lithium manganese iron phosphate material is 1-1.5 g / cm³. 3 .

16. A lithium manganese iron phosphate composite material, characterized in that, It includes the lithium manganese iron phosphate material as described in claim 14 or 15.

17. A positive electrode plate, characterized in that, The positive electrode comprises the lithium manganese iron phosphate material as described in claim 14 or 15.

Citation Information

Patent Citations

  • Lithium ion battery composite positive electrode material and preparation method

    CN112635722A

  • Lithium iron phosphate positive electrode material, preparation method thereof, and lithium ion battery

    US20240079573A1